SERANGAN HAMA PENGGEREK BATANG Ostrinia furnacalis Guenee (LEPIDOPTERA: PYRALIDAE) PADA VARIETAS JAGUNG DI KABUPATEN MINAHASA SELATAN - Inday Pangumpia; Jantje Pelealu; James B. Kaligis (COCOS, 2018)
Abstract The aim of this study was to determine the difference between O. furnacalis maize borer infestation on Pioneer 27 and Bisi 16 varieties in Kapitu, Amurang Barat, Tawaang, Tenga, Tenga, South Minahasa. The time for conducting the research is five months from February to June 2018. This study uses a survey research method with direct observation in farmers' plantations. Each farm is determined by one ha of corn plantations and then divided by five observation subplots that are spread diagonally and 40 subplots are taken.Â  Based on the results of the study, the percentage of O. furnacalis attacks on maize plants in Kapitu and Tawaang villages, South Minahasa regency, showed that based on varieties, the highest attack on maize variety was 27. P40, 0.40 percent, and Bisi 16 was only 0.23 percent. Percentage of attacks based on plant age shows that the corn bisi variety 16 at the age of plants 37 days after planting (HST) of 0.10%, 44 DAP of 0.25%, 51 DAP of 0.15%, 58 DAP of 0.27 % and 65 days after 0.39%. Furthermore, the percentage of attack of maize pioneer variety 27, namely 37 dap for 0.17%, 44 dap for 0.40%, 51 dap for 0.15%, 58 dap for 0.54% and 65 dap for 0.77%. The difference in O. furnacalis attack on varieties of corn plants, allegedly caused by eating and physical plants.